Artery of Adamkiewicz: a meta-analysis of anatomical characteristics - Taterra, Dominik; Skinningsrud, Bendik; Pękala, Przemysław A; Hsieh, Wan Chin; Cirocchi, Roberto; Walocha, Jerzy A; Tubbs, R Shane; Tomaszewski, Krzysztof A; Henry, Brandon Michael (Neuroradiology, 2019)
PURPOSE: The artery of Adamkiewicz (AKA) provides the major blood supply to the anterior thoracolumbar spinal cord and iatrogenic injury or inadequate reconstruction of this vessel during vascular and endovascular surgery can result in postoperative neurological deficit due to spinal cord ischemia. The aim of this study was to provide comprehensive data on the prevalence and anatomical characteristics of the AKA. METHODS: An extensive search was conducted through the major electronic databases to identify eligible articles. Data extracted included study type, prevalence of the AKA, gender, number of AKA per patient, laterality, origin based on vertebral level, side of origin, morphometric data, and ethnicity subgroups. RESULTS: A total of 60 studies (n = 5437 subjects) were included in the meta-analysis. Our main findings revealed that the AKA was present in 84.6% of the population, and patients most frequently had a single AKA (87.4%) on the left side (76.6%) originating between T8 and L1 (89%). CONCLUSION: As an AKA is present in the majority of the population, caution should be taken during vascular and endovascular surgical procedures to avoid injury or ensure proper reconstruction. All surgeons operating in the thoracolumbar spinal cord should have a thorough understanding of the anatomical characteristics and surgical implications of an AKA.
Keywords: Spinal Cord; arterie; hrudní obratle; Humans; Lumbar Vertebrae; mícha; bederní obratle; Arteries; lidé; Thoracic Vertebrae